Predicting the mesiodistal width of unerupted canine and premolars by using width of the permanent mandibular incisors and first molar in the Himachal population - Sudhir Mittal; Anirudh Pathak; Kavita Mittal; Vasundhara Pathania (Wolters Kluwer Medknow Publications, 2016)
Introduction: The determination of tooth size to arch length discrepancy in mixed dentition requires an accurate prediction of mesiodistal width of unerupted permanent teeth. Presently available methods use only the mesiodistal width of mandibular incisors. Melgaco (2007) introduced a new method of estimating width of unerupted canine and premolars by using mesiodistal width of incisors and first permanent molar. Aim: The aim of this study is to determine linear regression equation for estimating the widths of mandibular permanent canines and premolars using mesiodistal width of mandibular incisors and first molars in the Himachal population. Materials and Methods: Dental casts of 250 subjects were selected from the Himachal population who had fully erupted mandibular permanent incisors, canine, premolar, and first molar. Actual mesiodistal width of all fully erupted teeth were measured with digital vernier caliper and the values obtained were subjected to statistical and regression analysis. Results: High values of correlation (0.957) were found while considering Melgaco's method. Conclusion: From this study, it can be evaluated that Melgaco's method gives better prediction of unerupted permanent canines and premolars, and the equation Y = 13.48 + 0.614X can be suggested for the present population.